ANALISIS NILAI TOLERANSI SISWA PADA MATA PELAJARAN IPAS KELAS IV (A) SDN 51 SINGKAWANG - Diah Safitri; Mertika; Nindy Citroresmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to find out: 1) An overview of the tolerance value between grade IV students of SDN 52 Singkawang in the subject of Science; 2) supporting factors and inhibiting factors faced by teachers in instilling the tolerance value of grade IV (A) SDN 52 Singkawang students in subjects (IPAS). The type of research used is qualitative research. This research was conducted at SDN 51 Singkawang. The subject of this research is the main informant is a grade IV student of SDN 51 Singkawang and the second informant is a grade IV homeroom teacher of SDN 51 Singkawang. The data collection techniques used are questionnaires, interviews and documentation. The results of the study show that (1) The tolerance value of students at SDN 51 Singkawang has been well embedded. Where the homeroom teacher of class IV has carried out his duties as a homeroom teacher well. The homeroom teacher always tries to give the best for his students in the classroom and outside the classroom; (2) The supporting factor is that the homeroom teacher applies a nationalism attitude in the child and the inhibiting factor is that there are introverted students. This has also been overcome by the homeroom teacher by rolling the seats for introverted students every day.